A disper(segui)ção da memória em Carandiru - Mariano, Daniel (Universidade Federal de São Carlos, 2019)
This assignment investigates, through the Analysis of Discourse by French orientation and through the concepts of erasure (ORLANDI, 2005) and lack of memory (PAVEAU, 2013, 2015), how the discursive memory mobilizes, interdiscursively, with other discourses, with the erasure and with the lack of memory in two narratives which deal with the reports about the Carandiru. So, the mobilized corpus is composed of some statements and linguistic expressions taken from the books "Estação Carandiru" and "Carcereiros" by Drauzio Varella. More specifically, we want to understand the relation between memory, erasure, and lack of memory in the production of meaning that deals with the Carandiru history inscribed in these assignments and their proximity to the implosion of the House of Detention in São Paulo. For the development of the research, we conducted a descriptive course of the corpus and an explanation of the theoretical concepts and during the analysis, we note that the authorship of Drauzio Varella is legitimized by the medical institution, the publishing market and the media and that his FD is affiliated to the scientific discourse, maintaining a discursive relation with the FD of the prisoners, the FD of the jailers and the religious discourse that confers a messianic aura to him. In addition, we note that erasure restricts certain events and discourses as part of the policy of silence settled by Varella in his two books. Thus, the descriptive and objective style interspersed with the terms of the medical knowledge that manage the discourses around the FD by Varella, the choice of which character could say during the narrative and the censorship of certain words end up contributing to the process of lack of memory for some sayings like the words "massacre" and "prison". In this sense, we defend that erasure is a discursive resource that assists and speeds up, in some cases, lack of memory. This became evident when we approximated the discursive memory inscribed in the two assignments, the implosion and the creation of the Youth Park [Parque da Juventude], these three elements erase, silence and demystify Carandiru as a prison.
La dispersión de la memoria en Carandiru
Keywords: Carandiru; Memória; Apagamento; Memory; Erasure; Lack of memory; LINGUISTICA, LETRAS E ARTES::LINGUISTICA